PENGARUH KUALITAS PRODUK, HARGA, PROMOSI, DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN BUSANA MUSLIM MEREK HEAVEN LIGHTS DI KOTA BOGOR - Mujito Mujito; Tika Kartika Asri; M. Zairin; Novita Anggraeni; Anisa Apriyanti (Economicus : Jurnal Ekonomi dan Manajemen, 2024)
This research aims to determine the effect of product quality, price, promotion, and brand image on purchasing decisions for Heaven Lights brand Muslim clothing in Bogor City. The result show that : 1) The product quality variable affects the purchase decision of Heaven Lights Muslim clothing in Bogor City with a tcount value of 3.802 ≥ t table (1.660) and a significance value of 0.000 ≤ 0.1. (2) The price variable has no effect on the purchase decision of Heaven Lights Muslim clothing in Bogor City with a tcount value of 1.067 ≤ t table (1.66) and a significance value of 0.289 ≥ 0.1. (3) The promotion variable has no effect on the purchase decision of Heaven Lights Muslim clothing in Bogor City with a tcount value of 1.558 ≤ t table (1.66) and a significance value of 0.122 ≥ 0.1. (4) The brand image variable affects the purchase decision of Heaven Lights Muslim clothing in Bogor City with a tcount value of 5.095 ≥ t table (1.66) and a significance value of 0.000 ≤ 0.1. (5) The variables of product quality, price, promotion, and brand image jointly influence the purchasing decision of Heaven Lights Muslim clothing in the city of Bogor with an Fhitung value of 94.561 ≥ Ftabel (2.00) and a significance value of 0.000 ≤ 0.1.